Educational Diplomacy in Practice: Embassy-School Collaboration and the Strategic Role of Indonesia's Education Attaché in Riyadh - Rinaldi, Cherry; Khamidi, Amrozi; Amalia, Kaniati (Journal of Innovation and Research in Primary Education, 2025)
This study explores the strategic synergy between the Embassy of the Republic of Indonesia (KBRI) in Riyadh and Sekolah Indonesia Riyadh (SIR) in advancing Indonesia's educational diplomacy agenda. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and document analysis to examine the role of the Atase Pendidikan dan Kebudayaan (Atdikbud) and institutional cooperation in promoting soft power through education. Findings show that educational diplomacy in Riyadh functions not only as a platform for academic instruction but also as a tool for cultural transmission and national branding. Between 2022 and 2024, more than ten joint programs were implemented, including cultural festivals, teacher training workshops, and local BIPA classes attended by over 150 Saudi participants. Teachers and principals emphasized that Atdikbud acts as “a bridge that connects policy and practice,” facilitating curriculum adaptation, digital learning initiatives, and cross-cultural engagement. Challenges such as bureaucratic constraints, cultural sensitivity, and limited resources were addressed through adaptive strategies, including digitalizing school administration (SISILN) and inter-ministerial coordination. SIR serves as a cultural outpost, strengthening national identity among Indonesian diaspora youth while promoting intercultural understanding. The study highlights that educational diplomacy is most effective when it integrates governmental policy, institutional commitment, and community participation. This research contributes to diplomacy studies by providing empirical evidence of how education can serve as a measurable form of Indonesia’s soft power, especially in culturally and politically sensitive contexts like Saudi Arabia. Recommendations include developing evaluation frameworks, expanding international cooperation, and sustaining support from the Ministry of Education and Ministry of Foreign Affairs to enhance the impact and continuity of Indonesian Overseas Schools as instruments of educational diplomacy.